Prasa lokalna – między misją a rynkiem - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The paper deals with the relation between the mission of local press and the market where this press operates and functions. This relation sometimes results in social tensions, or even conflicts. It should be borne in mind that the expectations of the market may have influence on the notion of mission and vice versa. It is important to answer the following question in this context: What is the influence these factors exert on local press? The mission and market are two categories that have a very different influence on the responsibilities of local press. The mission calls for general social objectives to be fulfilled. The market on the other hand encourages commercial and individual tasks.